2013
DOI: 10.1002/wrcr.20427
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage hypogene karstification in a mountain hydrologic system: A coupled thermohydrochemical model incorporating buoyant convection

Abstract: [1] The early stage of hypogene karstification is investigated using a coupled thermohydrochemical model of a mountain hydrologic system, in which water enters along a water table and descends to significant depth ($1 km) before ascending through a central high-permeability fracture. The model incorporates reactive alteration driven by dissolution/ precipitation of limestone in a carbonic acid system, due to both temperature-and pressuredependent solubility, and kinetics. Simulations were carried out for homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Therefore, we use an intermediate porosity of 0.01 in the fracture for the base case and vary porosity in sensitivity analyses. This discussion of flow‐weighted and volume‐weighted porosity and the cubic law to assign permeability is intended to inform the representation of a fracture within a numerical grid without using an extremely fine (∼1 mm) grid that resolves physical dimensions of the fracture aperture [ Chaudhuri et al ., ]. ϕfw=bϕfΔx ϕvw=ϕm(Δxb)+bϕfΔx …”
Section: An Expanded Model Of Long‐term Hf Fluid Migrationmentioning
confidence: 99%
“…Therefore, we use an intermediate porosity of 0.01 in the fracture for the base case and vary porosity in sensitivity analyses. This discussion of flow‐weighted and volume‐weighted porosity and the cubic law to assign permeability is intended to inform the representation of a fracture within a numerical grid without using an extremely fine (∼1 mm) grid that resolves physical dimensions of the fracture aperture [ Chaudhuri et al ., ]. ϕfw=bϕfΔx ϕvw=ϕm(Δxb)+bϕfΔx …”
Section: An Expanded Model Of Long‐term Hf Fluid Migrationmentioning
confidence: 99%
“…However, little work has been done to quantitatively model such systems. Birk et al (2005) examined the development of gypsum maze caves in an artesian setting, and a series of studies has examined dissolution under cooling and buoyantly driven flows (Andre & Rajaram 2005;Chaudhuri et al 2008Chaudhuri et al , 2013. Little mathematical modeling work has been done on sulphuric acid speleogenesis.…”
Section: The Next Generation Of Speleogenesismentioning
confidence: 99%
“…Modeling of conduit development by hydrothermal dissolution along localized cross-formational fractures (Andre & Rajaram 2005;Rajaram et al 2009) revealed that the thermal coupling between the fluid and rock also causes the suppression of the flow-growth feedback and speleogenetic competition soon after breakthrough. Another specific feature of hypogene speleogenesis is the great role of buoyancy circulation (Klimchouk 1997b(Klimchouk , 2007, which has been confirmed and thoroughly studied by thermohydrochemical modeling (Chaudhuri et al 2013).…”
Section: The Author Defines Hypogene Speleogenesis As the Formation Omentioning
confidence: 95%